Cohesion and Coherence in Undergraduate Students’ Argumentative Essays - Priangan, Aulia; Saleh, Mursid; Rukmini, Dwi (Universitas Negeri Semarang, 2020)
This study aims to investigate cohesion and coherence in argumentative essays written by undergraduate students at Syekh Nurjati state Islamic institute of Cirebon, West Java, Indonesia. This study used discourse analysis as a research design. Five argumentative essays were chosen based on purposive sampling. The five argumentative essays were analyzed using Halliday and Matthiessen (2014) theory that contributing to the cohesion of the text, namely cohesive devices. Then, it was analyzed using Thornbury (2005) theory about coherence. The results of this study showed that undergraduate students at Syekh Nurjati state Islamic institute of Cirebon tend to use reference more frequently than the other grammatical cohesive devices. From 755 occurrences of grammatical cohesive devices which presented in the five argumentative essays, 532 of them were in the form of reference. Besides, they also tend to use repetition more often than the other lexical cohesive devices in their argumentative essay. It always present in the five argumentative essays. Furthermore, the thematic progressions were organized well. It is showed by the occurrence of two or more thematic progressions in each argumentative essay.